Müller Glia in Retinal Development: From Specification to Circuit Integration - Tworig, Joshua M.; Feller, Marla B. (Frontiers in Neural Circuits, 2022)
Müller glia of the retina share many features with astroglia located throughout the brain including maintenance of homeostasis, modulation of neurotransmitter spillover, and robust response to injury. Here we present the molecular factors and signaling events that govern Müller glial specification, patterning, and differentiation. Next, we discuss the various roles of Müller glia in retinal development, which include maintaining retinal organization and integrity as well as promoting neuronal survival, synaptogenesis, and phagocytosis of debris. Finally, we review the mechanisms by which Müller glia integrate into retinal circuits and actively participate in neuronal signaling during development.